MR-Guided Adaptive Radiotherapy in Localized Prostate Cancer - Andrea Gaetano Allegra MD; Luca Nicosia MD; Michele Rigo MD; Nicola Bianchi BS; Riccardo Filippo Borgese BS; Antonio De Simone BS; Niccolò Giaj-Levra PhD; Davide Gurrera BS; Stefania Naccarato BS; Edoardo Pastorello MD; Francesco Ricchetti MD; Gianluisa Sicignano BS; et al. (Technology in Cancer Research & Treatment)
MR-guided radiotherapy (MRgRT) is novel treatment modality in Radiation Oncology that could allow a higher precision and tolerability of Radiation Treatments. This modality is possible due to dedicated systems consisting of a MR scanner mounted on a conventional linac and software that permit daily online treatment plan adaptation. Prostate cancer (PC) is one of the most common malignancies in RO clinical practice and currently under investigation with this new technology. The focus of this review is to describe the current state of the art and clinical results of MRgRT in the treatment of PC. The available technology are briefly described, as well as the published literature and possible future applications